ابن باديس ودور إصلاح التعليم بالزيتونة في الحفاظ على الهوية خلال الفترة الاستعمارية - مرابطي رفيقة; مرغيت محمد (University Of Eloued جامعة الوادي, 2023)
تعتبر مسألة الهوية من بين القضايا التي كانت مطروحة وسط الشعوب المغاربية، بسبب إهدار الاستعمار لمقوماتها ببعديها العربي والإسلامي وتكريسه للفراغ الثقافي والفكري، وكان بن باديس يدرك من خلال تتبعه لقضايا التربية والتعليم في جميع الأقطار المغاربية بأن تغيير هذه الأوضاع يستلزم ضرورة إصلاح الوضع التعليمي في المنطقة المغاربية، والتي أصبحت برامج مؤسساتها التعليمية عقيمة، خاصة جامع الزيتونة، وتجاوز ابن باديس النقد إلى تقديم البديل، بارسال مقترح برنامج إصلاحي متكامل للمؤسسة الزيتونية سنة 1931م، لتغيير المناهج والمواد العلمية، كي تتماشى مع تطور العصر، وتسد الفراغ المتعلق بثوابت الهوية المغاربية وتعزيز الانتماء الوطني، فما هي المقترحات التي قدمها ابن باديس في مشروعه لإصلاح التعليم بجامع الزيتونة؟ وفيما تتمثل مرتكزات الهوية في برنامجه التعليمي؟ وما هو دور هذه الإصلاحات في الحفاظ على الهوية المغاربية؟. The issue of identity is among the issues that were raised among the peoples of the Maghreb, due to the colonialism’s blurring of its components in its Arab and Islamic dimensions and its dedication to a cultural and intellectual void. Ben Badis was aware, through his followup to education issues in all Maghreb countries, that changing these conditions necessitates the need to reform the educational situation in the region. Magharebia, And whose educational institutions’ programs became ineffective, especially the Zaytouna Mosque, and Ibn Badis went beyond criticism to offer an alternative, by sending a proposal for an integrated reform program to the Zaytouna Institution in 1931, To change the curricula and scientific materials, in order to keep pace with the development of the times, and fill the void related to the constants of Maghreb identity and the strengthening of national belonging, What are the proposals made by Ibn Badis in his project to reform education at AlZaytouna Mosque? What are the foundations of identity in his educational program? What is the role of these reforms in preserving the Maghreb identity?
Keywords: ابن باديس; جامع الزيتونة; التعليم; الإصلاح; الهوية; Ibn Badis; Al-Zaytouna Mosque; education; repair; identity